HIGH RESISTANCE IN UROPATHOGENS ISOLATED FROM CHILDREN AT PAKISTANI HOSPITAL - Zahra Naz; Alia Batool; Abdul Rauf et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT: Urinary tract infection is one of the most important clinical infections in the world. Due to empirical therapy, antibiotic resistance pattern has been altered in the causative microbes of urinary tract infection in childhood. The objective of this study was to ﬁnd out causative agents of urinary tract infection in children and their antimicrobial proﬁle. A total of 1370 urine samples were collected and identiﬁed by standard microbiological techniques. Antimicrobial susceptibility of isolates was performed according to CLSI 2012 guidelines. Signiﬁcant bacterial count was found in 8.32% children. Most common isolated pathogens were Escherichia coli (60.5%) and Klebsiella pneumoniae (26.3%). Pathogens were resistant to ceﬁxime (83%), ceftriaxone (81%) and amoxicillin-clavulanic acid (69%). Acinetobacter baumannii were found most resistant. Meropenem, amikacin and piperacillin-tazobactam were most eﬀective. It is concluded that multidrug resistant organisms causing UTI in children in our locality. It is suggested that local surveillance studies should be done continuously to screen antimicrobial resistance.